The mediating effect of attitude on factors affecting the recycling behavior of Malaysian youth - Wok, Saodah; Ithnin, Norjasmin (Communication Department, Faculty of Modern Languages, Universiti Putra Malaysia, 2018)
The reception to youths to the Malaysian government recycling programs is poor; what more, their participation. As such, this study tries to investigate the mediating effect of attitude towards recycling behavior among youths. The objectives of the study are (1) to determine the level of awareness, perception, perceived cleanliness-related issues, attitude and behavior on recycling, (2) to analyze the relationships between awareness, perception, perceived cleanliness-related issues and attitude with recycling behavior, and (3) to test the mediating effect of attitude on awareness, perception and perceived cleanliness-related issues on recycling behavior. The study uses the quantitative research design and employs the survey method for data collection. Questionnaires are distributed to Malaysian youths in Kuala Lumpur. Results show that youths have a positive awareness, perception, perceived cleanliness-related issues, attitude and behavior on recycling. The relationships between behavior with awareness, perception, perceived cleanliness-related issues, and attitude are positive and significant. However, attitude is only able to mediate the relationship between perception and behavior on recycling. To a certain extent, the social learning theory holds true for the study. It is suggested that the government should promote the recycling campaign through television, newspaper and the Internet.